THE STUDY OF CUSTOMER SATISFACTION AMONG GRAB USERS IN KUALA LUMPUR, MALAYSIA - Kurniawati , Atheria; Raj, Michele Shivaanii Sundra; Singh, Jugindar Singh Kartar (Electronic Journal of Business and Management, 2021)
The emergence of the sharing economy has disrupted traditional industries, particularly tourism and transportation. On-demand ride-hailing services like Grab have become significant threats to traditional taxi companies by utilizing technology to connect providers and customers seamlessly. Beyond technology, the sharing economy is often praised for being more affordable, convenient, and environmentally sustainable. This study investigates how three prominent pillars of the sharing economy—economic, social, and environmental factors—influence customer satisfaction among Grab users in Kuala Lumpur. It aims to determine if the growth of these platforms is driven by genuine satisfaction or mere curiosity toward brand innovation.